Clinical trial awareness and participation attitudes among patients with epidermolysis bullosa and their caregivers: a nationwide cross-sectional study from Saudi Arabia - Ashjan Alheggi; Saifaleslam A. Mahmoud; Danah Alali; Abrar Bukhari; Salma Albargawi; Rayan Alkhodair; Christine Wagger; Sophie Kitzmueller (Frontiers in Medicine, 2026)
Background Epidermolysis bullosa (EB) is a rare, inherited skin fragility disorder with significant disease burden and rapidly evolving therapeutic options. Clinical trial recruitment in rare diseases remains challenging; understanding patient perspectives is essential to designing patient-centred protocols. The objective of this study was to explore clinical trial awareness, motivators, and barriers among patients with EB and their caregivers in Saudi Arabia. Materials and methods This cross-sectional study recruited participants of all EB subtypes and ages from the Saudi EB Registry. A 40-item structured, self-administered questionnaire assessed clinical background, knowledge and attitudes toward clinical trials, motivators and barriers for participation. Responses were recorded on a five-point Likert scale. Data were analysed using IBM SPSS Statistics version 23. Results Thirty-five participants were enrolled; 68.6% were younger than 18 years and 57.1% of questionnaires were completed by caregivers. Knowledge about EB clinical trials was low in 80% of participants; the level of knowledge was statistically significantly associated with the desire to participate ( p = 0.001). Despite low knowledge, willingness to participate was high or very high in 51.4% of participants. Practical motivators ranked highest; travel and accommodation cost coverage and better medical care during the study period were rated as highly important by 94.3% each. Altruistic motivators followed closely; contributing to increased disease knowledge and future improvements for other patients with EB were highly important to 91.4% and 88.6% respectively. The dominant barriers were distance and travel costs and concern about being in the placebo group (65.7% each), followed by lack of clear information about the study protocol (62.9%). Conclusions This study provides the characterisation of clinical trial awareness, motivators, and barriers among patients with EB and their caregivers. Patient education is the most actionable target for improving trial recruitment. The high prioritisation of symptom alleviation underscores the importance of incorporating patient-reported outcome measures as primary or co-primary endpoints in future EB trial design. Trial protocols in EB should minimise travel burden and invasive procedures, address paediatric-specific barriers including route of administration, frequency, and school absenteeism, and incorporate flexible, patient-centred designs to optimise enrolment across the EB community.